2023
DOI: 10.3390/applmicrobiol3030065
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Rhizobacterial Isolates from Apple Rhizosphere for Their Biocontrol and Plant Growth Promotion Activity

Salma Jabiri,
Ikram Legrifi,
Majda Benhammou
et al.

Abstract: Apple crops are prone to several diseases that limit their production—in particular, root rot caused by a new genus of oomycetes, mainly Phytopythium vexans. This study aims to screen antagonistic bacteria that can play an important role in the biological control of this pathogenic oomycete and to evaluate their capacity to promote plant growth. The dual culture test revealed that, out of 200 bacterial isolates, 16 have been able to inhibit the mycelial growth of P. vexans with inhibition rates greater than 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 94 publications
0
1
0
Order By: Relevance
“…In particular, the B. subtilis strain ZH1 showed in this study demonstrated the great potential of wild-type strains for the production of biosurfactants as representatives of bioactive metabolites. Nevertheless, more ecological sites are available for the identification of novel strains with promising gene clusters encoding for bioactive metabolites, such as the rhizosphere, which makes them interesting for application as biopesticides [77,78].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, the B. subtilis strain ZH1 showed in this study demonstrated the great potential of wild-type strains for the production of biosurfactants as representatives of bioactive metabolites. Nevertheless, more ecological sites are available for the identification of novel strains with promising gene clusters encoding for bioactive metabolites, such as the rhizosphere, which makes them interesting for application as biopesticides [77,78].…”
Section: Discussionmentioning
confidence: 99%